A new phytophagous Bracon Fabricius (Hymenoptera, Braconidae) associated with Protium ovatum Engl. (Burseraceae) fruits from Brazilian savannah - Perioto, Nelson Wanderley; Lara, Rogéria Inês Rosa; Ferreira, Cleidson Soares; Fernandes, Daniell Rodrigo Rodrigues; Pedroso, Elizabeth Do Carmo; Volpe, Haroldo Xavier Linhares; Nais, Juliana; Correa, Lilian Roberta Batista; Viel, Silvio Rogério (Zootaxa, 2011)
Bracon zuleideae Perioto & Lara sp. nov. (Hymenoptera, Braconidae), a new species of phytophagous braconid associated with fruits of Protium ovatum Engl. (Burseraceae) is described and illustrated.